The Escherichia coli type III secretion system 2 Is involved in the biofilm formation and virulence of avian Pathogenic Escherichia coli. (December 2021) - Yin, Lei; Li, Qianwen; Wang, Zeping; Shen, Xuehuai; Tu, Jian; Shao, Ying; Song, Xiangjun; Qi, Kezong; Pan, Xiaocheng
Abstract: The Escherichia coli type III secretion system 2 (ETT2) is found in most pathogenic E. coli strains. Although many ETT2 gene clusters carry multiple genetic mutations or deletions, ETT2 is known to be involved in bacterial virulence. To date, no studies have been conducted on the role of ETT2 in the virulence of avian pathogenic Escherichia coli (APEC), which harbours ETT2. Thus, we deleted the ETT2 of APEC strain and evaluated the phenotypes and pathogenicities of the mutant. The results showed that deletion of ETT2 had no effect on APEC growth, but significantly promoted biofilm formation. In addition, as compared to the wild-type （WT） strain, the ETT2 deletion significantly promoted adherence to and invasion of DF-1 chicken fibroblasts and facilitated survival in the sera of specific-pathogen-free chickens. Analysis of the role of ETT2 in animal infection models demonstrated that the distribution of viable bacteria in the blood and organs of chicks infected with the ΔETT2 was significantly higher than those infected with WT. The results of RNA sequencing indicated that multiple genes involved in biofilm formation, lipopolysaccharide components, fimbrial genes and virulence effector proteins are regulated by ETT2. Collectively, these results implicated ETT2 is involved in the biofilm formation and pathogenicity of APEC. Highlights: The ETT2 is crucial for bacterial serum resistance, adhesion and invasion. We have demonstrated ETT2 plays an important role in biofilm formation and virulence of APEC. The results will help to further elucidate the mechanism employed by the ETT2 to devise strategies for therapy.